Accuracy assessment of a GPS device for maximum sprint speed - Alphin, K.; Sisson, O.; Hudgins, B. L.; Noonan, C. D.; Bunn, J. A. (International Journal of Exercise Science, 2020)
Global positioning system (GPS) technology can capture maximum sprint speed (MSS) using fewer resources than electronic timing gates (ETG). Yet,errors with GPS technology are typically 1.01 km·hr-1for instantaneous velocity, potentially limiting GPS accuracy. The purpose of this study was to compare MSS values obtained from GPS technology to those obtained from ETG. The MSS of 24 female athletes was determined using two tests that both began with a 20-m fly-in followed by: 1) 80-m maximal sprint with ETG placed at the start line, 30 m, 60 m, and 80 m, and 2) 30-m maximal sprint with ETG placed every 10 m. Sprint speed was calculated from each timing segment, and the fastest segment for each test was used for the calculated MSS. MSS was also obtained using a GPS unit measuring at 10 Hz. Mean bias and mean absolute percent error (MAPE) of the GPS was lower for the 80-m test (0.09 ± 1.24km·hr-1,3.5 ±3.1%) than the 30-m test(1.58 ± 0.80 km·hr-1, 5.5 ± 2.6%).Lin`s concordance agreement was found to be poor for both tests. The equivalence test indicated that the GPS was equivalent for both short and long distances, p< .05, meaning the two results were within a 5% equivalence interval. The GPS devices were within the acceptable range of accuracy at short (10-m) and long (30-m) distances. These results can guide coaching staff regarding how to test their athlete`s metrics and the reliability of those results.